Tamoxifen Use Correlates with Increased Risk of the First Episode of Ischemic Cerebrovascular Disease in Older Women with Breast Cancer: A Case-Control Study in Taiwan - Lai, Shih-Wei; Lin, Cheng-Li; Liao, Kuan-Fu (Frontiers in Pharmacology, 2017)
Background and Objectives. There are inconsistent results about the association between ischemic cerebrovascular disease and tamoxifen use in women with breast cancer. The study aimed to evaluate the association between the risk of ischemic cerebrovascular disease and tamoxifen use in older women with breast cancer in Taiwan. Methods. We designed a retrospective, nationwide, case-control study using the database of the Taiwan National Health Insurance Program. A total of 800 female subjects with breast cancer aged ≥ 65 years with the first episode of ischemic cerebrovascular disease from 2000 to 2011 were identified as the cases. Additionally, 2876 female subjects with breast cancer aged ≥ 65 years without any type of cerebrovascular diseases were selected as the control subjects. The cases and the control subjects were matched with age and comorbidities. Ever use of tamoxifen was defined as subjects who had at least a prescription for tamoxifen before the index date. Never use of tamoxifen was defined as subjects who never had a prescription for tamoxifen before the index date. We used the multivariable logistic regression model to calculate the odds ratio (OR) and 95% confidence interval (CI) for ischemic cerebrovascular disease associated with tamoxifen use. Results. After adjusting for confounding variables, the adjusted OR of ischemic cerebrovascular disease was 2.5 for subjects with ever use of tamoxifen (95% CI 2.10, 2.97), compared with never use of tamoxifen. In addition, the adjusted OR of ischemic cerebrovascular disease was 1.15 (95% CI 1.10, 1.21) in subjects with ever use of tamoxifen as increase in use duration per one year. The adjusted OR of ischemic cerebrovascular disease was 2.54 (95% CI 2.03, 3.17) in subjects with ever use of tamoxifen as increase in dosage per one milligram. Conclusions. Tamoxifen use is significantly associated with 2.5-fold increased odds of ischemic cerebrovascular disease among older women with breast cancer in Taiwan. There are duration-dependent and dose-dependent effects of tamoxifen use on the risk of ischemic cerebrovascular disease.